COMPETITIVE ADSORPTION, DISPLACEMENT, AND TRANSPORT OF ORGANIC MATTER ON IRON OXIDE: II. DISPLACEMENT AND TRANSPORT - Gu B.; Mehlhorn T.L.; Liyuan L.; McCarthy J.F. (My University, 1996)
The competitive interactions between organic matter compounds and mineral surfaces are poorly understood, yet these interactions may play a significant role in the stability and co-transport of mineral colloids and/or environmental contaminants. In this study, the processes of competitive adsorption, displacement, and transport of Suwannee River natural organic matter (SR-NOM) are investigated with several model organic compounds in packed beds of iron oxide-coated quartz columns. Results demonstrated that strongly-binding organic compounds are competitively adsorbed and displace those weakly-bound organic compounds along the flow path. Among the four organic compounds studied, polyacrylic acid (PAA) appeared to be the most competitive, whereas SR-NOM was more competitive than phthalic and salicylic acids. The transport of SR-NOM is found to involve a complex competitive interaction and displacement of different NOM subcomponents. A diffuse adsorption and sharp desorption front (giving an appearance of irreversible adsorption) of the SR-NOM breakthrough curves are explained as being a result of the competitive time-dependent adsorption and displacement processes between different organic components within the SR-NOM. The stability and transport of iron oxide colloids varied as one organic component competitively displaces another. Relatively large quantities of iron oxide colloids are transported when the more strongly-binding PAA competitively displaces the weakly-binding SR-NOM or when SR-NOM competitively displaces phthalic and salicylic acids. Results of this study suggest that the chemical composition and hence the functional behavior of NOM (e.g., in stabilizing mineral colloids and in complexing contaminants) can change along its flow path as a result of the dynamic competitive interactions between heterogeneous NOM subcomponents. Further studies are needed to better define and quantify these NOM components as well as their roles in contaminant partitioning and transport.